IMPROVEMENT OF THE ORGANIZATIONAL-ECONOMIC MECHANISM OF MANAGEMENT OF ENTERPRISES OF THE FUEL-ENERGY COMPLEX - M. A. Ostashkin (Модернизация, инновация, развитие)
In the modern period of the change of the scale and nature of the competition, which is acquiring an international character, serious question about ensuring the sustainable development ofRussia. The most important factor that ensures the sustainable development of the country, is to increase the efficiency and competitiveness of industrial enterprises. Modern organizational-economic mechanisms of management of enterprises of the energy sector of the Russian economy are studied in the works of such economists as S.N. Ivanov, Loginov E., Solonitsyn A.G., Khlebnikov V., Cherkasenko A.I. An abundance of research points to the relevance and topicality of the problem. In this article considers the ways of improvement of organizational-economic mechanism of management of enterprises of the fuel-energy complex of theRussian Federation.